A Rare Infection Post Hyaluronic Acid Injection in the Trochanter: Case Report and Literature Review - Mohamed Badie Ahmed (10223510) (2024)
Filler injection has become a commonplace aesthetic procedure. Although the incidence of infection following filler injections is typically low, ranging between 0.04% and 0.2%, the potential consequences can be serious. In this manuscript, we present the case of a 29-year-old female patient who presented to our emergency department after receiving a hyaluronic acid filler injection in the trochanteric area at a private center. She developed signs and symptoms shortly after the procedure, including bilateral hip pain and a fever that persisted for 3 days. Despite initial antibiotic and pain medication treatment, the patient’s condition continued to worsen. Incision and drainage were performed, and pus culture revealed profuse Extended Spectrum Beta-Lactamase (ESBL)-producing Serratia marcescens. The patient experienced clinical improvement following the incision and drainage procedure and initiation of antibiotics sensitive to the pathogen. Although rare, S. marcescens infection following filler injections has been reported in 2 previous cases. Therefore, early recognition of infection signs and symptoms is crucial to mitigate the severity of consequences and improve outcomes. Aggressive surgical and medical interventions, such as incision and drainage, debridement, and appropriate antibiotic therapy, may be necessary to achieve a successful outcome. Other Information Published in: Aesthetic Surgery Journal Open Forum License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/asjof/ojae052